c - Bhattoji Diksita; Vasu, Srisa Chandra, 1861-1918?; t; t (Delhi : Motilal Banarsidass Publishers Private Limited, 2014)
Classical commentary on A{u3CB4}$1!wE(Bhy$1!8[!{,(Bof P$1-8J(Bnini, compendium of Sanskrit language grammar.s
Originally published: 1906.
English and Sanskrit.
Keywords: Panini; Sanskrit language -- Grammar